2020
DOI: 10.1111/1752-1688.12895
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Effects of Forest Harvesting on Sediment Yield in Forested Watersheds of the United States

Abstract: Managed forests generally produce high water quality, but degradation is possible via sedimentation if proper management is not implemented during forest harvesting. To mitigate harvesting effects on total watershed sediment yield, it is necessary to understand all processes that contribute to these effects. Forest harvesting best management practices (BMPs) focus almost exclusively on overland sediment sources, whereas in‐and‐near stream sources go unaddressed although they can contribute substantially to sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 250 publications
(390 reference statements)
0
12
0
Order By: Relevance
“…Land‐cover change can impact suspended‐sediment loads directly, through increased sediment delivery associated with hillslope disturbance, or indirectly, in cases where increased discharge results in higher sediment transport capacity and/or accelerated erosion of in‐channel sediment sources (Lewis et al, 2001; McEachran et al, 2021; Reid et al, 2010; Safeeq et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Land‐cover change can impact suspended‐sediment loads directly, through increased sediment delivery associated with hillslope disturbance, or indirectly, in cases where increased discharge results in higher sediment transport capacity and/or accelerated erosion of in‐channel sediment sources (Lewis et al, 2001; McEachran et al, 2021; Reid et al, 2010; Safeeq et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined how these ecosystem services are generally affected by various environmental and management factors (Felzer et al, 2004;Pan et al, 2009;Nunery and Keeton, 2010;Dangal et al, 2014;Lu et al, 2015). For forest water dynamics, previous studies have examined how timber harvests or land conversions have influenced runoff (Khand and Senay, 2021;McEachran et al, 2021). This study is the first to examine how extreme climate events influence these ecosystem services and how changes in forest NBI from these factors influence the response of forest ecosystems to later extreme climate events.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, Cienciala et al (2022) found thatsimilar to the findings of research reviewed abovea mountainous basin affected by such timber harvest operations experienced one order of magnitude changes in sediment yield. Over time, better management practices, associated with a changing regulatory and policy framework, seem to have moderated the impact of forest operations on slope stability in the region (Amaranthus et al, 1985;Beschta and Jackson, 2008;Cristan et al, 2016;McEachran et al, 2021).…”
Section: Slope Movements and Denudationmentioning
confidence: 99%
“…There seems to be a similar coupling between HGP and global geomorphic change, and some data suggest a decoupling is taking place, to some extent. Several lines of evidence point in this direction: reduction of landslide frequency in the last 10-20 years mentioned by Rivas et al (2022), clearly not attributable to rainfall decrease; lower frequency of slope failures observed in the Pacific NW (Beschta and Jackson, 2008;Cristan et al, 2016;McEachran et al, 2021); global reduction of disasters related to geomorphic processes in general, during the last decade (Cendrero et al, 2020). They are all scarcely explainable by rainfall change, and suggest that impacts on land are being reduced, or mitigation measures implemented.…”
Section: Perspectivesmentioning
confidence: 99%